Potret Perempuan dalam Novel Manusia Bebas Karya Suwarsih Djojopuspito - Ridwan, Ridwan; Ramadhani, Fitri (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2025)
This research aims to express the portrait of women in the novel Manusia Bebas by analyzing the feminist literary criticism approach that provides another space in literary appreciation and criticism. The analysis conducted by examining the novel Manusia Bebas by Suwarsih Djojopoespito uses the repeated reading method and the qualitative descriptive method so that it is possible to open up space for interpretation regarding female characters and their position in the novel. The qualitative research method is also known as the interpretative method because the research data is more related to the interpretation of the data found in the field. The results of the research on the novel "Manusia Bebas" by Suwarsih Djojopoespito found Sulastri's role as a child, Sulastri's role in society, and Sulastri's role as a wife. The most basic role for a child is to respect their parents. But this obedience is not always absolute. Sulastri is committed to fighting for the right to education for the community by establishing folk schools or private schools and choosing freedom outside the lines. In order to support and achieve her goal, she supported Sudarmo even though she had to live with hardship. Even so, Sulastri was still a critical woman who also criticized her own husband to also urge him to prosper her as his wife and child.